Alex Vatank, Iran and Pakistan: Security, Diplomacy and American Influene - Mr. Sajid Aziz (CISS Insight Journal, 2016)
Iran and Pakistan relations have had some distinct charateristics over the last six decades. Unlike India and Afghanistan, Iran does not have contested borders with Pakistan, but their bilateral relationship is marred by geopolitical rivalry, economic disconnect and deep distrust of each other. Their rhetoric of shared cultural history going centuries back is contrasted to the diametrically opposed political outlooks on contemporary security and regional issues. The era of cooperation during the Shah’s era when Iran and Pakistan were both part of Central Treaty Organization(CENTO) and their shared strategic interests of containing ’communist expansion’ after the Soviet invasion of Afghanistan, was followed by a zero-sum game in Afghanistan, which still, in a more moderate form, continues. The most concrete manifestations of these features of their bilateral relationship are the partially successful visit of President Rouhani to Pakistan, tripartite trade agreement between Iran, India and Afghanistan, bypassing Pakistan and more importantly the failure of both states to open a new page after the Joint Comprehensive Plan of Action (JCPA) commonly known as Iran nuclear deal and the subsequent lifting of sanctions on Iran. Alex Vatanka, a Senior fellow at the the Middle East Institute and Jamestown Foundation in Washington, in his book Iran and Pakistan: Security, Diplomacy and American Influence, captures all these aspects of Pakistan-Iran relations. But more importantly Vatanka discusses these issues in the larger geopolitical context, regional situation and the role of outside powers generally and American influence particularly. Expanded over ten chapters, the book covers the history of Pak-Iran bilateral relations from 1959 when Pakistan and Iran signed the ’Friendship Treaty’ to the contemporary period. Written in crisp prose, the chrological order of events is interspersed with insighful analyses that take into account not only the overlapping of security challenges, threat perceptions of both the states and the geopolitics of that era but also factors in the role of leadership at the helm of affairs that shaped the policies of the respective states.